2019
DOI: 10.7554/elife.41814
|View full text |Cite
|
Sign up to set email alerts
|

A calcium transport mechanism for atrial fibrillation in Tbx5-mutant mice

Abstract: Risk for Atrial Fibrillation (AF), the most common human arrhythmia, has a major genetic component. The T-box transcription factor TBX5 influences human AF risk, and adult-specific Tbx5-mutant mice demonstrate spontaneous AF. We report that TBX5 is critical for cellular Ca2+ homeostasis, providing a molecular mechanism underlying the genetic implication of TBX5 in AF. We show that cardiomyocyte action potential (AP) abnormalities in Tbx5-deficient atrial cardiomyocytes are caused by a decreased sarcoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 51 publications
4
32
0
Order By: Relevance
“…Recent studies investigating the cellular mechanisms of AF have suggested that abnormal atrial calcium handling contributes to AF pathogenesis, leading to trigger formation (56,(58)(59)(60). Although SR calcium content is affected by both SERCA uptake and RYR2-mediated calcium leak, our previous study suggested that Ryr2 binding was not affected in Tbx5 knockout mice, suggesting a primary role of SERCA in TBX5-dependent calcium dysfunction (61). Consistent with this model, increased SERCA activity by reduced PLN, an SERCA inhibitor, rescued the Tbx5-haploinsufficient phenotype ( Figure 5).…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies investigating the cellular mechanisms of AF have suggested that abnormal atrial calcium handling contributes to AF pathogenesis, leading to trigger formation (56,(58)(59)(60). Although SR calcium content is affected by both SERCA uptake and RYR2-mediated calcium leak, our previous study suggested that Ryr2 binding was not affected in Tbx5 knockout mice, suggesting a primary role of SERCA in TBX5-dependent calcium dysfunction (61). Consistent with this model, increased SERCA activity by reduced PLN, an SERCA inhibitor, rescued the Tbx5-haploinsufficient phenotype ( Figure 5).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, adult-restricted Tbx5-mutant mice demonstrated spontaneous AF, and in Tbx5-deficient atrial cardiomyocytes, action potential abnormalities occurred due to a decreased SERCA2-mediated sarcoplasmic reticulum calcium uptake (Dai et al, 2019). In human beings, TBX5 is highly expressed in embryonic and postnatal hearts (Hatcher et al, 2000), and a number of TBX5 loss-or gain-of-function mutations have been causally linked to HOS, including CHD and AF as well as cardiac block (Al-Qattan and Abou Al-Shaar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that changes in Pitx2 levels lead to electrical remodelling linked to arrhythmogenesis (2) and that Pitx2 regulates membrane effector genes associated with the electrical remodelling in a dose-dependent manner (3,7,8). Therefore, based on the correlation of the Pitx2 levels with remodelled parameters observed in previous studies (3,4,7,8,41) and the correlation of remodelled parameters with changes in APs in the present study, the correlation of the Pitx2 levels with different AF models can be built. In the previous studies, Pitx2 deficiency is associated with the increase in G Na , G up (8) and G CaL (41) and the reduction in G K1 (4).…”
Section: The Correlation Of Pitx2 Levels With Different Af Modelsmentioning
confidence: 81%
“…Therefore, based on the correlation of the Pitx2 levels with remodelled parameters observed in previous studies (3,4,7,8,41) and the correlation of remodelled parameters with changes in APs in the present study, the correlation of the Pitx2 levels with different AF models can be built. In the previous studies, Pitx2 deficiency is associated with the increase in G Na , G up (8) and G CaL (41) and the reduction in G K1 (4). Interestingly, our simulated results indicated that the incidence of triggered AP was negatively correlated with G Ks and G K1 and was positively correlated with G Na , G CaL and G up .…”
Section: The Correlation Of Pitx2 Levels With Different Af Modelsmentioning
confidence: 97%
See 1 more Smart Citation